Physical Function Following Megaprosthesis Surgery in the Lower Limb—A Prospective Cohort Study of 38 Patients - Sarah Stammose Freund, MD, PhD; Michael Melchior Bendtsen, MD, PhD; Bjarne Hauge Hansen, MD; Henning Andersen, MD, PhD; Thomas Baad-Hansen, MD, PhD (Arthroplasty Today, 2025)
Background: Limited knowledge exists on early outcomes postmegaprosthesis surgery. Yet, understanding these outcomes is crucial for patient counseling. This prospective study investigates physical function outcomes in lower limb megaprosthesis surgery patients, employing both objective and subjective measures and explores associations between them. Methods: A total of 38 patients underwent treatment with a proximal femur, distal femur, or proximal tibia megaprosthesis. Muscle strength tests, range of motion, Timed Up and Go test, and the Musculoskeletal Tumor Society score were conducted at 4, 8, and 12-18 months postsurgery. Repeated measurements analysis was performed along with a comparison between treated limb, untreated limb, and predictive values. Results: Bilateral muscle strength reduction was observed, with the proximal tibia group showing the most pronounced deficits. None of the groups exhibited changes in strength over time. All groups had decreased joint flexion in the treated limb compared to the untreated limb 12-18 months postsurgery. Timed Up and Go performance improved in all groups, but remained below average compared to reference values. An association was observed between a lower Timed Up and Go Test and higher Musculoskeletal Tumor Society scores, with the latter being lowest in the proximal tibia group. Conclusions: This study provides comprehensive first-year outcome data following megaprosthesis surgery, offering valuable information to guide patient care. Markedly reduced strength in both treated and untreated limbs compared to predicted normal values was observed. The significant deficit in walking ability was clearly associated with patient-reported outcomes.